Designing taxi ridesharing systems with shared pick-up and drop-off locations: Insights from a computational study - Stumpe, Miriam; Dieter, Peter; Schryen, Guido; Müller, Oliver; Beverungen, Daniel (Transportation Research Part A: Policy and Practice)

Leveraging Business Modeling Tools For Ecosystemic Business Model Design - Vorbohle, Christian; Kundisch, Dennis (Journal of Business Models)

Anwendung von System Dynamics zur Geschäftsmodellinnovation in einem B2B-Ökosystem - Ksouri-Gerwien, Christoph; Vorbohle, Christian (Digitale Plattformen und Ökosysteme im B2B-Bereich)

Do Country Risk Factors Attenuate the Effect of Tax Loss Incentives on Corporate Risk-Taking? - Osswald, Benjamin; Sureth-Sloane, Caren
This study investigates whether country risk factors, including political and fiscal budget risk, attenuate the effectiveness of tax policy tools that aim to encourage corporate risk-taking. Exploiting a cross-country panel, we predict and find that the effectiveness of loss offset rules and tax rate changes is fully attenuated for firms located in high-risk countries. We document the attenuating effect of country risk is more pronounced in high-tax countries or when countries increase their corporate tax rate. Additional tests around the U.S. federal budget crises from 2011 to 2013 indicate that temporarily heightened fiscal budget risk attenuates the effectiveness of loss offset rules even in countries with low political risk. We identify conditions (low political and low fiscal budget risk) under which targeted tax policy tools effectively stimulate risk-taking. This suggests that ensuring taxpayers receive tax refunds is important in times of economic crises with budgetary or political challenges.

An Integrated Fuzzy Analytic Network Process and Fuzzy Regression Method for Bitcoin Price Prediction - Amiri, Arman; Tavana, Madjid; Arman, Hosein (Internet of Things)
Keywords: Management of Technology and Innovation; Artificial Intelligence; Computer Science Applications; Hardware and Architecture; Engineering (miscellaneous); Information Systems; Computer Science (miscellaneous); Software

Data-driven simulation-based decision support system for resource allocation in industry 4.0 and smart manufacturing - Mahmoodi, Ehsan; Fathi, Masood; Tavana, Madjid; Ghobakhloo, Morteza; Ng, Amos H.C. (Journal of Manufacturing Systems)
Keywords: Industrial and Manufacturing Engineering; Hardware and Architecture; Software; Control and Systems Engineering

A systematic review of the soft computing methods shaping the future of the metaverse - Tavana, Madjid; Sorooshian, Shahryar (Applied Soft Computing)
Keywords: Software

Einführung - Wortmann, Fabio; Kämmerling, Sina; Hemmrich, Simon; Gradert, Till; Ellermann, Kai (Digitale Plattformen im industriellen Mittelstand. Strategien, Methoden, Umsetzungsbeispiele)

Grundlagen - Hemmrich, Simon; Wortmann, Fabio; Lüttenberg, Hedda; Gradert, Till; Kämmerling, Sina; Meyer, Maurice (Digitale Plattformen im industriellen Mittelstand. Strategien, Methoden, Umsetzungsbeispiele)

What Price Culture? – A Taxonomy of the Admission Pricing Policy at Museums - Althaus, Maike; Müller, Stefanie Jutta Marianne; Kundisch, Dennis (International Journal of Cultural Policy)
An admission pricing policy should allow a museum to facilitate access to cultural education and heritage while contributing to its economical sustainability. Despite the importance of this matter to museums, design-relevant knowledge on the configuration of the admission pricing policy in museums remains limited, resulting in museum decision-makers lack the necessary understanding of how to customize their admission pricing policy, and researchers the foundation for advancing knowledge on the topic. To address these issues, we draw on a well-established development method to build a taxonomy, which involved synthesising the literature on the admission pricing policy of museums, analysing the characteristics of the admission pricing policy of 149 museums, and creating a cluster analysis for 117 museums located in the same region. The analysis yielded three distinct clusters (namely, free admission pricing policy, simple admission pricing policy, comprehensive admission pricing policy). Our work supports practitioners by showing them different options for structuring an admission pricing policy, while providing researchers with a foundation for further investigating museums’ admission pricing policies.

Hierarchical Taxonomies in Information Systems - Nickerson, Robert C.; Varshney, Upkar; Muntermann, Jan; Kundisch, Dennis (Proceedings of Thirtieth Americas Conference on Information Systems (AMCIS))

Time perspectives and collaborative performance in creative tasks - Auer, Thorsten Fabian; Hoppe, Julia Amelie; Thommes, Kirsten (Journal of Organizational Effectiveness: People and Performance)
Purpose The relationship between variation in time perspectives and collaborative performance is scarcely explored, and even less is known about the respective mechanisms that lead to varying task performance. Thus, we aim to further the literature on time perspectives and collaborative performance, shedding light on the underlying behavioral patterns. Design/methodology/approach We report a quasi-experiment analyzing the impact of past, present and future orientation variation in dyads ( N = 76) on their quantitative and qualitative performance when confronted with a simple incentivized creative task with constraints. Subsequently, we offer a qualitative analysis of comments given by the participants after the task on the collaboration. Findings Results indicate that a dyad's elevation of past orientation and diversity in future orientation negatively affect collaborative performance. At the same time, there is a positive effect of elevation of future orientation. The positive effect is driven by clear communication and agreement during the task, while the negative effect arises from work sharing and complementation. Practical implications This study provides insights for organizations on composing individuals regarding their temporal focus for collaborative tasks that should be executed rapidly and require creative solutions. Originality/value Our study distinguishes by considering the composition of past, present and future time perspectives in dyads and focuses on a creative task setting. Moreover, we explore the mechanisms in the dyads with a substantial elevation of/diversity in future orientation, leading to their stronger/weaker performance.
Keywords: Organizational Behavior and Human Resource Management

Can leaders motivate employees’ energy-efficient behavior with thoughtful communication? - Hoffmann, Christin; Thommes, Kirsten (Journal of Environmental Economics and Management)
Keywords: Management; Monitoring; Policy and Law; Economics and Econometrics

Komplexität von Verrechnungspreisen und Tax Compliance: Einblicke in deutsche Unternehmen - Greil, Stefan; Kaluza-Thiesen, Eleonore; Schulz, Kim Alina; Sureth-Sloane, Caren (Deutsches Steuerrecht)

Playing games with QCA: Measuring the explanatory power of single conditions with the Banzhaf index - Haake, Claus-Jochen; Schneider, Martin (Journal of International Management)
Qualitative comparative analysis (QCA) enables researchers in international management to better understand how the impact of a single explanatory factor depends on the context of other factors. But the analytical toolbox of QCA does not include a parameter for the explanatory power of a single explanatory factor or “condition”. In this paper, we therefore reinterpret the Banzhaf power index, originally developed in cooperative game theory, to establish a goodness-of-fit parameter in QCA. The relative Banzhaf index we suggest measures the explanatory power of one condition averaged across all sufficient combinations of conditions. The paper argues that the index is especially informative in three situations that are all salient in international management and call for a context-sensitive analysis of single conditions, namely substantial limited diversity in the data, the emergence of strong INUS conditions in the analysis, and theorizing with contingency factors. The paper derives the properties of the relative Banzhaf index in QCA, demonstrates how the index can be computed easily from a rudimentary truth table, and explores its insights by revisiting selected papers in international management that apply fuzzy-set QCA. It finally suggests a three-step procedure for utilizing the relative Banzhaf index when the causal structure involves both contingency effects and configurational causation.
Keywords: Qualitative comparative analysis; Banzhaf power index; causality; explanatory power

Rechtstatsachen im Privatrecht

Die Leiden des jungen (Datenaus-) Werthers - Einblicke in die Praxis der empirischen Rechtsforschung - Bartlitz, David (Rechtstatsachen im Privatrecht)

On the Capacity of Artificial Intelligence Techniques and Statistical Methods to Deal with Low Quality Data in Medical Supply Chain Environments - Santos-Arteaga, F.J.; Di Caprio, D.; Tavana, Madjid; Cucchiari, D.; Campistol, J.M.; Oppenheimer, F.; Diekmann, F.; Revuelta, I. (Engineering Applications of Artificial Intelligence)

A Full Ranking Method in Data Envelopment Analysis with Multi-Criteria Decision Analysis - Tavana, Madjid; Bonyani, A.; Karimi, T. (International Journal of Applied Management Science)

A Two-Level Supply Chain Coordination Model for Perishable Products under Optimal Markdown Time and Trade Credit Policies - Setak, M.; Tavana, Madjid; Talafi Daryani, H. (OPSEARCH)

A Novel Fuzzy General Best-Worst Method for Considering Diversity and Inclusion in Supplier Selection Programs - Tavana, Madjid; Sorooshian, S.; Sarvarizadehkouhpaye, M.; Mina, H. (Annals of Operations Research)

Einführung in das Bürgerliche Recht

Data Envelopment Analysis: From Non-Monotonic to Monotonic Scale Elasticities - Dellnitz, A.; Tavana, Madjid (European Journal of Operational Research)

§ 78 (Kartellrechtliche Grenzen der stillen Gesellschaft) - Bartlitz, David (Münchener Handbuch des Gesellschaftsrechts)

§ 6 (Kartellrechtliche Grenzen der Kommanditgesellschaft) - Bartlitz, David (Münchener Handbuch des Gesellschaftsrechts)

Gesetz über digitale Märkte (Digital Markets Act) - Bartlitz, David; Gräfe, Alexander (Handbuch des EU-Wirtschaftsrechts)

§ 16 a (Girokonto und Zahlungsdiensterahmenvertrag) - Bartlitz, David (Verbraucherrecht)

The conditional impact of market consolidation and market power on banking stability – Evidence from Europe - Herwald, Sarah; Voigt, Simone; Uhde, André (Journal of Risk Finance)
Purpose Academic research has intensively analyzed the relationship between market concentration or market power and banking stability but provides ambiguous results, which are summarized under the concentration-stability/fragility view. We provide empirical evidence that the mixed results are due to the difficulty of identifying reliable variables to measure concentration and market power. Design/methodology/approach Using data from 3,943 banks operating in the European Union (EU)-15 between 2013 and 2020, we employ linear regression models on panel data. Banking market concentration is measured by the Herfindahl–Hirschman Index (HHI), and market power is estimated by the product-specific Lerner Indices for the loan and deposit market, respectively. Findings Our analysis reveals a significantly stability-decreasing impact of market concentration (HHI) and a significantly stability-increasing effect of market power (Lerner Indices). In addition, we provide evidence for a weak (or even absent) empirical relationship between the (non)structural measures, challenging the validity of the structure-conduct-performance (SCP) paradigm. Our baseline findings remain robust, especially when controlling for a likely reverse causality. Originality/value Our results suggest that the HHI may reflect other factors beyond market power that influence banking stability. Thus, banking supervisors and competition authorities should investigate market concentration and market power simultaneously while considering their joint impact on banking stability.
Keywords: market concentration; market power; banking stability; European banking

Green Multi-Objective Scheduling - A memetic NSGA-III for flexible production with real-time energy cost and emissions - Burmeister, Sascha Christian

The Imperative of Revival Strategies through Digital Transformation in the Cultural Sector - A Taxonomy Approach - Althaus, Maike; Hansmeier, Philipp (Proceedings of the Thirty-Second European Conference on Information Systems (ECIS 2024))

Understanding cognitive decline in older ages: The role of health shocks - Schiele, Valentin; Schmitz, Hendrik (European Economic Review)
Individual cognitive functioning declines over time. We seek to understand how adverse physical health shocks in older ages contribute to this development. By use of event-study methods and data from the USA, England, and several countries in Continental Europe, we find evidence that health shocks lead to an immediate and persistent decline in cognitive functioning. This robust finding holds in all regions representing different health insurance systems and seems to be independent of underlying individual demographic characteristics such as sex and age. We also ask whether variables that are susceptible to policy action can reduce the negative consequences of a health shock. Our results suggest that neither compulsory education nor retirement regulations moderate the effects, thus emphasizing the importance for cognitive functioning of maintaining good physical health in old age.

Location-Based Service and Location-Contextualizing Service: Conceptualizing the Co-creation of Value with Location Information - zur Heiden, Philipp; Priefer, Jennifer; Beverungen, Daniel (Proceedings of the 56th Conference on System Sciences)

Supporting Business Model Decision-making in B2B Ecosystems: A Framework for Using System Dynamics - Ksouri-Gerwien, C.; Vorbohle, Christian (Proceedings of the 55th Hawaii International Conference on System Sciences (HICSS))

Distortional effects of separate accounting and formula apportionment on factor allocation - Ortmann, Regina; Pummerer, Erich (Journal of Business Economics)
Abstract We examine distortions caused by tax base allocation systems–separate accounting (SA) or formula apportionment (FA)–with respect to the allocation of assets and workforce within multinational entities (MNEs). The effects of both systems are intensively debated by EU Member States as they are striving to implement a European tax system. Its introduction would lead to a switch from SA to FA. Moreover, Pillar One of the recent global tax reform includes a mix of both tax base allocation systems. We find that, against the claims of the EU, FA does not necessarily create lower distortions of the factor allocation. Decisive for that assessment is the level of profit shifting under SA. Our results indicate that, in tendency, the factor allocation is more severely distorted by FA when the profit shifting possibilities were rather low under SA. In contrast to former studies, we highlight the importance of analyzing the status quo under the recently applied system (SA) in order to be able to assess the consequences of a switch from SA to FA. Our results are interesting for policy-makers as they help anticipating reactions of MNEs to a change in the applied tax base allocation system and for companies as a basis for future tax planning.
Keywords: Economics and Econometrics; Business and International Management

Beste Bedingungen für junge Ökonominnen und Ökonomen? Neue Daten und Empfehlungen der Arbeitsgruppe “Nachwuchs” im Verein für Socialpolitik - Bayer, Christian; Englmaier, Florian; Riphahn, Regina; Schmidt-Dengler, Philipp; Sondergeld, Virgina; Sureth-Sloane, Caren; von Wangenheim, Jonas; Weizsäcker, Georg (Perspektiven der Wirtschaftspolitik)
Der Verein für Socialpolitik hat zur Bearbeitung seines Schwerpunktthemas „Nachwuchs“ für die Dauer der Kalenderjahre 2021-2022 eine Arbeitsgruppe eingerichtet – im Folgenden: AG Nachwuchs –, deren Aufgabe das Vorlegen eines umfassenden Berichts zur Situation der VWL-Promovierenden und -PostDocs im DACH-Raum ist. Gestützt auf Datenerhebungen und strukturierte Interviews formuliert die AG Nachwuchs in diesem Bericht zwei Empfehlungen, jeweils eine für den Doc- und den PostDoc-Bereich. Sie empfiehlt im PostDoc-Bereich, dass die Fakultäten bzw. verwandte VWL-Einrichtungen den Übergang zu Tenure-Track beschleunigen und ihn durch eine systematische Planung der Zahlenverhältnisse zwischen den Karrierestufen bei ihrem wissenschaftlichen Personal begleiten. Dadurch sollen bessere Karriereperspektiven erreicht werden. Sowohl die befragten Nachwuchskräfte als auch die befragten Professor:innen und Programmleitungen betonen die Thematik der Stellenperspektiven stark. Im Doc-Bereich dokumentieren die Erhebungsdaten eine überraschend geringe Zufriedenheit der VWL-Promovierenden mit der Betreuungssituation durch die Professorenschaft. Die AG Nachwuchs empfiehlt daher eine höhere Betreuungsdichte und eine stärkere Vernetzung von Promovierenden. Weitere Hilfestellungen für Promovierende können in Mehrfach- oder Teambetreuungen sowie in der Bereitstellung von Informationen über die Vielfalt möglicher Karrierewege bestehen.

Isolating Personal Knowledge Spillovers: Coinventor Deaths and Spatial Citation Differentials - Balsmeier, Benjamin; Fleming, Lee; Lück, Sonja (American Economic Review: Insights)
We propose a new method to estimate and isolate the localization of knowledge spillovers due to the physical presence of a person, using after-application but pre-grant deaths of differently located coinventors of the same patent. The approach estimates the differences in local citations between the deceased and still-living inventors at increasingly distant radii. Patents receive 26 percent fewer citations from within a radius of 20 miles around the deceased, relative to still-living coinventors. Differences attenuate with time and distance, are stronger when still-living coinventors live farther from the deceased, and hold for a subsample of possibly premature deaths. (JEL O31, O33, O34, R32)
Keywords: Management; Monitoring; Policy and Law; Geography; Planning and Development

Zur Effektivität des europäischen Kronzeugenprogramms - Der Fall des LKW-Kartells - Tiessen, Michelle

Towards an Amended Arm´s Length Principle - Tackling Complexity and Implementing Destination Rules in Transfer Pricing - Greil, Stefan; Overesch, Michael; Rohlfing-Bastian, Anna; Schreiber, Ulrich; Sureth-Sloane, Caren (Intertax)

Who benefits from quality competition in health care? A theory and a laboratory experiment on the relevance of patient characteristics - Brosig-Koch, Jeannette; Hehenkamp, Burkhard; Kokot, Johanna (Health Economics)
We study how competition between physicians affects the provision of medical care. In our theoretical model, physicians are faced with a heterogeneous patient population, in which patients systematically vary with regard to both their responsiveness to the provided quality of care and their state of health. We test the behavioral predictions derived from this model in a controlled laboratory experiment. In line with the model, we observe that competition significantly improves patient benefits as long as patients are able to respond to the quality provided. For those patients, who are not able to choose a physician, competition even decreases the patient benefit compared to a situation without competition. This decrease is in contrast to our theoretical prediction implying no change in benefits for passive patients. Deviations from patient-optimal treatment are highest for passive patients in need of a low quantity of medical services. With repetition, both, the positive effects of competition for active patients as well as the negative effects of competition for passive patients become more pronounced. Our results imply that competition can not only improve but also worsen patient outcome and that patients’ responsiveness to quality is decisive.
Keywords: physician competition; patient characteristics; heterogeneity in quality responses; fee-for-service; laboratory experiment

Price Regulation, Quality Competition and Location Choice with Costly Relocation - Hehenkamp, Burkhard; Kaarbøe, Oddvar M.
We consider a model where for-profit providers compete in quality in a price-regulated market that has been opened to competition, and where the incumbent is located at the center of the market, facing high costs of relocation. The model is relevant in markets such as public health care, education and schooling, or postal services. We find that, when the regulated price is low or intermediate, the entrant strategically locates towards the corner of the market to keep the incumbent at the low monopoly quality level. For a high price, the entrant locates at the corner of the market and both providers implement higher quality compared to a monopoly. In any case, the entrant implements higher quality than the incumbent provider. Social welfare is always higher in a duopoly if the cost of quality is low. For higher cost levels welfare is non-monotonic in the price and it can be optimal to the regulator not to use its entire budget. Therefore, the welfare effect of entry depends on the price and the size of the entry cost, and the regulator should condition the decision to allow entry on an assessment of the entry cost.
Keywords: Quality competition; Price regulation; Location choice; Product differentiation

Distribution Network Optimization: Predicting computation times to design scenario analysis for network operators - Burmeister, Sascha Christian; Schryen, Guido (Energy Systems)

Business Models for Cultural Event Platforms – A Taxonomy Approach - Althaus, Maike; Müller, Michelle; Vorbohle, Christian; Kundisch, Dennis (Proceedings of the International Conference on Challenges in Managing Smart Products and Services (CHIMSPAS 2023))

May I have your Attention, please? – The Interaction between Attention Screening and Reputation on Crowdworking Platforms - Laux, Florian; Poniatowski, Martin; Kundisch, Dennis (Proceedings of the 31st European Conference on Information Systems (ECIS))

Designing Business Reputation Ecosystems — A Method for Issuing and Trading Monetary Ratings on a Blockchain - Hemmrich, Simon; Bobolz, Jan; Beverungen, Daniel; Blömer, Johannes (ECIS 2023 Research Papers)
Market transactions are subject to information asymmetry about the delivered value proposition, causing transaction costs and adverse market effects among buyers and sellers. Information systems research has investigated how review systems can reduce information asymmetry in business-to-consumer markets. However, these systems cannot be readily applied to business-to-business markets, are vulnerable to manipulation, and suffer from conceptual weak spots since they use textual data or star ratings. Building on design science research, we conceptualize a new class of reputation systems based on monetary-based payments as quantitative ratings for each transaction stored on a blockchain. Using cryptography, we show that our system assures content confidentiality so that buyers can share and sell their ratings selectively, establishing a reputation ecosystem. Our prescriptive insights advance the design of reputation systems and offer new paths to understanding the antecedents, dynamics, and consequences to reduce information asymmetry in B2B transactions.

Supporting Innovation through B2B Reviews – A Taxonomy of B2B Online Review Environments - Seutter, Janina; Bartelheimer, Christian; Kundisch, Dennis (Proceedings of the 18th International Conference on Design Science Research in Information Systems and Technology)

Updating at the Expense of Demand? The Case of Platform Apps - Jabr, Wael; Gutt, Dominik; Neumann, Jürgen; Kundisch, Dennis (Proceedings of the 45th ISMS Marketing Science Conference)

HIEF: a holistic interpretability and explainability framework - Kucklick, Jan-Peter (Journal of Decision Systems)
Many applications are driven by Machine Learning (ML) today. While complex ML models lead to an accurate prediction, their inner decision-making is obfuscated. However, especially for high-stakes decisions, interpretability and explainability of the model are necessary. Therefore, we develop a holistic interpretability and explainability framework (HIEF) to objectively describe and evaluate an intelligent system’s explainable AI (XAI) capacities. This guides data scientists to create more transparent models. To evaluate our framework, we analyse 50 real estate appraisal papers to ensure the robustness of HIEF. Additionally, we identify six typical types of intelligent systems, so-called archetypes, which range from explanatory to predictive, and demonstrate how researchers can use the framework to identify blind-spot topics in their domain. Finally, regarding comprehensiveness, we used a random sample of six intelligent systems and conducted an applicability check to provide external validity.
Keywords: Explainable AI (XAI); machine learning; interpretability; real estate appraisal; framework; taxonomy

Digitale Transformation im Theater – Mittels Besucherforschung und Entscheidungsunterstützung zur besseren Angebotsgestaltung - Kempkes, Jens Peter; Kreuzhage, Katharina; Kundisch, Dennis; Seutter, Janina; Weskamp, Christoph

Crowdwork in the Age of Algorithms – How Algorithmic Requesters affect the Meaningfulness of Crowdwork - Laux, Florian; Haff, André; Kundisch, Dennis

Literature Reviews in Operations Research: A New Taxonomy and a Meta Review - Schryen, Guido; Sperling, Martina (Computers & Operations Research)

Integrating driver behavior into last-mile delivery routing: Combining machine learning and optimization in a hybrid decision support framework - Dieter, Peter; Caron, Matthew; Schryen, Guido (European Journal of Operational Research (EJOR))

Architectural Management of OTF Computing Markets - Gottschalk, Sebastian; Vorbohle, Christian; Kundisch, Dennis; Engels, Gregor; Wünderlich, Nacy V. (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

The Market for Services: Incentives, Algorithms, Implementation - Haake, Claus-Jochen; Hehenkamp, Burkhard; Polevoy, Gleb (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

Empirical Analysis in Markets for OTF Services - Elrich, Alina; Kaimann, Daniel; Fahr, René; Kundisch, Dennis; Mir Djawadi, Behnud; Müller, Michelle; Poniatowski, Martin; Schäfers, Sabrina; Frick, Bernd (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

Zusatzkosten der Besteuerung – Eine Analyse des steuerlichen Verwaltungsaufwands und der subjektiv wahrgenommenen Steuerbelastung - Fochmann, Martin; Heinemann-Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren (Steuer und Wirtschaft)

Anticipatory Assignment of Passengers to Meeting Points for Taxi-Ridesharing - Dieter, Peter; Stumpe, Miriam; Ulmer, Marlin Wolf; Schryen, Guido (Transportation Research Part D)

Gelingensbedingungen gestaltungsorientierter Schulentwicklung - Schwabl, Franziska; Daniel-Söltenfuß, Desiree (Organisation zwischen Theorie und Praxis)

„Allowing the Economy to Breathe Even During the Crisis“ – Interview with Tax Expert Caren Sureth-Sloane - Unterstell, Rembert (german research – Magazine of the Deutsche Forschungsgemeinschaft)

#DIGITALENTS - Digital Talents Programm geht in die zweite Runde - Kundisch, Dennis

Digitale Transformation im Theater – Mittels Besucherforschung und Entscheidungsunterstützung zur besseren Angebotsgestaltung - Kempkes, J. P.; Kreuzhage, K.; Kundisch, Dennis; Seutter, Janina; Weskamp, Christoph (Kultur Management Network Magazin)

Life-cycle health effects of compulsory schooling - Schmitz, Hendrik; Tawiah, Beatrice Baaba
We study the effect of education on health (hospital stays, number of diagnosed conditions, self-rated poor health, and obesity) over the life-cycle in Germany, using compulsory schooling reforms as a source of exogenous variation. Our results suggest a positive correlation of health and education which increases over the life-cycle. We do not, however, find any positive local average treatment effects of an additional year of schooling on health or health care utilization for individuals up to age 79. An exception is obesity, where positive effects of schooling start to be visible around age 60 and become very large in age group 75-79. The results in age group 75-79 need to be interpreted with caution, however, due to small sample size and possible problems of attrition.
Keywords: Education; health; life-cycle effects; compulsory schooling

Housing Situations and Local COVID-19 Infection Dynamics – A Case Study With Small-Area Data - Freise, Diana; Schiele, Valentin; Schmitz, Hendrik
Keywords: General Earth and Planetary Sciences; General Environmental Science

The effect of compulsory schooling on vaccination against COVID and Influenza - Monsees, Daniel; Schmitz, Hendrik
We study the effect of education on vaccination against COVID-19 and influenza in Germany and Europe. Our identification strategy makes use of changes in compulsory schooling laws and allows to estimate local average treatment effects for individuals between 59 and 91 years of age. We find no significant effect of an additional year of schooling on vaccination status in Germany. Pooling data from Europe, we conclude that schooling increases the likelihood to vaccinate against COVID by an economically negligible effect of one percentage point (zero for influenza). However, we find indications that additional schooling increases fear of side effects from COVID vaccination.
Keywords: COVID; influenza; vaccination; education; compulsory schooling

Unboxing video effectiveness – Does speech matter? - Garnefeld, I.; Böhm, Eva; Hanf, L.; Helm, S. (2023 AMA Summer Academic Conference, San Francisco, CA)

The dark and bright side of online reviews in manufacturer online shops - Kessing, K.; Garnefeld, I.; Böhm, Eva (EMAC Annual Conference, Odense, Denmark)

Stimulating engagement with unboxing videos – Does speech matter? - Hanf, L.; Garnefeld, I.; Böhm, Eva; Helm, S. (EMAC Annual Conference, Odense, Denmark)

Bring me my Meal on your Wheel - An Empirical Analysis of the Impact of Food Delivery Platforms on Local Restaurant Employment - Müller, Michelle; Neumann, Jürgen (Proceedings of the 55th Hawaii International Conference on System Sciences (HICSS))

Digital technology usage as a driver of servitization paths in manufacturing industries - Harrmann, Lisa Katharina; Eggert, Andreas; Böhm, Eva (European Journal of Marketing)
Purpose This study aims to conceptually propose and empirically validate a path perspective on the servitization process of manufacturing firms. It identifies a customer and an outcome path to servitization, sheds light on the pivotal role of digital technology usage for both value-creating paths and explores their financial and relational performance outcomes. Design/methodology/approach The authors use a mixed-method approach, combining a qualitative study with a cross-sectional survey in the USA, the UK and Germany. Findings Manufacturing firms choose between two generic paths to servitization, a customer and an outcome path. Digital technology usage is equally important for both value-creating paths. Progress on the outcome path has a positive effect on firms’ financial performance, whereas the customer path has an indirect effect only, fully mediated by firms’ relational performance. Customer tenure and customer’s open-mindedness are contingency variables in the digital technology usage – servitization path – firm performance framework. Research limitations/implications A path perspective is useful to conceptualize the servitization processes in manufacturing industries. Future research should investigate the sequential choice of servitization paths and explore its drivers and performance outcomes. Practical implications To create and claim superior value for their customers, managers can choose between two servitization paths, leading to differential performance outcomes. While digital technology usage is key to progress on both paths, it is particularly effective for newly acquired customers on the customer path. Suppliers should target their value-creating service offerings at open-minded customer firms to reap their full performance potential. Originality/value Propose and empirically validate a path-perspective on servitization. Understand the pivotal importance of digital technology usage for both servitization paths.
Keywords: Marketing

Der Hauptschulabschluss als sozial selektiver Hauptzulieferer des Übergangssystems - Sommer, Christian (Berufsbildung. Zeitschrift für Theorie-Praxis-Dialog)
Über zwei Drittel der Anfänger*innen im Übergangssystem verfügen maximal über einen Hauptschul-/Mittelschulabschluss. Sie sind damit überrepräsentiert, was sich weniger durch ihre Kompetenzen als mit ihrem sozioökonomischen Status und klassenspezifischen Nachqualifizierungsverhalten erklären lässt.
Keywords: Social inequality; Transition system

A Regret Policy for the Dynamic Vehicle Routing Problem with Time Windows - Dieter, Peter (Lecture Notes in Computer Science)

Housing situations and local COVID-19 infection dynamics using small-area data - Freise, Diana; Schiele, Valentin; Schmitz, Hendrik (Scientific Reports)
Abstract Low socio-economic status is associated with higher SARS-CoV-2 incidences. In this paper we study whether this is a result of differences in (1) the frequency, (2) intensity, and/or (3) duration of local SARS-CoV-2 outbreaks depending on the local housing situations. So far, there is not clear evidence which of the three factors dominates. Using small-scale data from neighborhoods in the German city Essen and a flexible estimation approach which does not require prior knowledge about specific transmission characteristics of SARS-CoV-2, behavioral responses or other potential model parameters, we find evidence for the last of the three hypotheses. Outbreaks do not happen more often in less well-off areas or are more severe (in terms of the number of cases), but they last longer. This indicates that the socio-economic gradient in infection levels is at least in parts a result of a more sustained spread of infections in neighborhoods with worse housing conditions after local outbreaks and suggests that in case of an epidemic allocating scarce resources in containment measures to areas with poor housing conditions might have the greatest benefit.
Keywords: Multidisciplinary

Implementing Digital Responsibility through Information Systems Research: A Delphi Study of Objectives, Activities, and Challenges in IS Research - Beverungen, Daniel; zur Heiden, Philipp; Lehrer, Christiane; Trier, Matthias; Bartelheimer, Christian; Bradt, Tobias; Distel, Bettina; Drews, Paul; Ehmke, Jan Fabian; Fill, Hans-Georg; Flath, Christoph M.; Fridgen, Gilbert; et al.

The Origination of Online Reviews in B2B Markets: A Qualitative Study on the Underlying Motives of Review Writers - Seutter, Janina

Wie Arbeitgeber strategisch gegen den Arbeitskräftemangel vorgehen. - Schneider, Martin; Radermacher, Katharina (Wie Arbeitgeber strategisch gegen den Arbeitskräftemangel vorgehen.)

The Role of Response Time for Algorithm Aversion in Fast and Slow Thinking Tasks - Lebedeva, Anastasia; Kornowicz, Jaroslaw; Lammert, Olesja; Papenkordt, Jörg (Artificial Intelligence in HCI)

Are Numbers or Words the Key to User Reliance on AI? - Papenkordt, Jörg; Ngonga-Ngomo, Axel-Cyrille; Thommes, Kirsten (Academy of Management Proceedings)

Employer Branding - Wie Arbeitgeber strategisch gegen den Arbeitskräftemangel vorgehen. - Schneider, Martin; Radermacher, Katharina (Die Politische Meinung)

A model of cycles and bubbles under heterogeneous beliefs in financial markets - Burs, Carina (Cogent Economics & Finance)
I study the effect of heterogeneous beliefs about asset prices on the long-term behavior of financial markets. Starting from the ideas of Abreu and Brunnermeier (Citation2003), a two-dimensional system of differential equations is developed. The first dynamic variable is the asset price growth rate. The second dynamic variable is the number of investors who believe that asset prices are abnormally high. In a phase plane analysis, I find both stable and unstable equilibria, depending on the spread of information and the response to other agents’ beliefs. If individuals try to increase their returns while perceiving more overpricing, these equilibria can be spirals or even approach limit cycles. Although I intend to study general price patterns, abnormally high asset prices can be caused by financial bubbles. In this model, bubbles can emerge and deflate both in cycles or directly, or they can grow until they burst. Further, I analyze market behavior after a central bank increases the interest rate. This can lead to new stable equilibria, but the emergence and bursting of bubbles cannot be prevented.
Keywords: asset pricing; subjective information; stability conditions; monetary policy; risk aversion

Frühe Versuche zur Etablierung des Hochschulstandorts Paderborn (1945-1970) - Grüttner, Niclas Christian (50 Jahre Universität Paderborn. Studentische Forschungsprojekte zur Gründungsgeschichte. Ein Rückblick)

The Choice of Ideology and Everyday Decisions - Burs, Carina; Gries, Thomas; Müller, Veronika (Journal of Organizational Psychology)
Individuals strive to make decisions that are consistent with not only their consumer preferences but also their psychological needs. However, they are confronted with complex, ambiguous or even false information. Ideologies and belief systems provide guidance when processing and evaluating information and give a coherent and comprehensible interpretation of reality. The first question is: why is an individual attracted to a particular ideology? Individuals choose ideologies that resonate with their subjective psychological needs and preferences. Second, how do individuals search for ideologies and find out which suit them best? We model an individual’s sequential information search for the best matching ideologies by applying Bayesian learning and utility optimization. Additional information enhances utility by reducing uncertainty. As a search is costly, the process may stop once an individual adopts an ideology even if the information set remains incomplete. Third, once they have chosen a particular ideology, individuals adhere to its rules and norms when making everyday decisions. Consumers not only physically consume, but they also act in accordance with their psychological needs.
Keywords: Economics; Ideology; Decision-making

Erlebnisorientiert Lehren und Lernen in der beruflichen Bildung. Entwicklung eines didaktischen Konzepts im Rahmen von designbasierter Forschung. - Volgmann, Simone

An IAD framework analysis of minigrid institutions for sustainable rural electrification in East Africa: A comparative study of Uganda and Tanzania - Namujju, Lillian Donna; Acquah-Swanzy, Henrietta; Ngoti, Irene F. (Energy Policy)
Keywords: Management; Monitoring; Policy and Law; General Energy

A Memetic NSGA-II for the Multi-Objective Flexible Job Shop Scheduling Problem with Real-time Energy Tariffs - Burmeister, Sascha Christian; Guericke, Daniela; Schryen, Guido (Flexible Services and Manufacturing Journal)

GBP-Monitor: Betriebswirtschaftliche Einschätzungen und Erwartungen von Unternehmen in Deutschland. Unternehmenstrends im November 2023 - Maiterth, Ralf; Sureth-Sloane, Caren; Dyck, Daniel; Heinemann-Heile, Vanessa

Frühe Versuche zur Etablierung des Hochschulstandorts Paderborn (1945-1970) - Grüttner, Niclas Christian (50 Jahre Universität Paderborn. Studentische Forschungsprojekte zur Gründungsgeschichte. Ein Rückblick)

Reviewing from a Distance: Uncovering Asymmetric Moderations of Spatial and Temporal Distances Between Sentiment Negativity and Rating - Neumann, Jürgen; Gutt, Dominik; Kundisch, Dennis (MIS Quarterly)

Collective Minimum Contributions to Counteract the Ratchet Effect in the Voluntary Provision of Public Goods - Alt, Marius; Kesternich, Martin; Gallier, Carlo; Sturm, Bodo (Journal of Environmental Economics and Management)
We experimentally test a theoretically promising amendment to the ratchet-up mechanism of the Paris Agreement. The ratchet-up mechanism prescribes that parties’ commitments to the global response to climate change cannot decrease over time, and our results show that its effect is detrimental. We design a public goods game to study whether cooperation is promoted by an amendment to the mechanism that stipulates that all agents must contribute at least a collectively chosen minimum based on the principle of the lowest common denominator. We find that binding collective minimum contributions improve the effectiveness of the ratchet-up mechanism. Non-binding minimum contributions, by contrast, do not encourage cooperation. Our data indicate that the difference is attributable to conditional cooperative dynamics. If other participants contribute less than the collective minimum contribution, even initially cooperative participants start to negatively reciprocate this form of non-compliance by contributing less.
Keywords: global public goods; climate change; institutions; ratchet-up mechanism; minimum contributions; laboratory experiment

Role (in-)congruity and the Catch 22 for female executives: how stereotyping contributes to the gender pay gap at top executive level - Diederich, Sarah; Iseke, Anja; Pull, Kerstin; Schneider, Martin (The International Journal of Human Resource Management)
Keywords: Management of Technology and Innovation; Organizational Behavior and Human Resource Management; Strategy and Management; Business and International Management; Industrial relations

Inter-Charity Competition under Spatial Differentiation: Sorting, Crowding, and Spillovers - Gallier, Carlo; Goeschl, Timo; Kesternich, Martin; Lohse, Johannes; Reif, Christiane; Römer, Daniel (Journal of Economic Behavior and Organization)

Digital Responsibility – a Multilevel Framework for Responsible Digitalization - Beverungen, Daniel; Kundisch, Dennis; Mirbabaie, Milad; Müller, Oliver; Schryen, Guido; Trang, Simon Thanh-Nam; Trier, Matthias (Business & Information Systems Engineering)

Who Will Own Our Global Digital Twin: The Power of Genetic and Biographic Information to Shape Our Lives - Hellweg, Talea Davina; Schneider, Martin; Rückert, Ulrich; Harteis, Christian; Pilz, Sarah (The Digital Twin of Human)
Today, it is possible to collect and connect large amounts of digital data from various sources and life domains. This chapter examines the potential and the risks of this development from an interdisciplinary perspective. It defines the ‘global digital twin’ of a human being as the sum of all digitally stored information and predictive knowledge about a person. It points out that, compared to the digital twin of a machine, the human global digital twin is far more complex because it comprises the genetic code and the biographic code of a person. The genetic code contains not only a simple ‘construction plan’ but also hereditary information, in a form that is difficult to read. The biographic code contains all other information that can be assembled about a person, which is obtained via data from cameras, microphones, or other sensors, as well as general personal information. When the growing wealth of information concerning the genetic code and the biographical code is properly utilised, insights from biology and the behavioural sciences may be used to predict personal events such as health problems, job resignations, or even crimes. Because our own interests and those of private firms are partly in conflict over the use of this powerful knowledge, it is still unclear whether the global digital twins of humans will become a liberating or disciplining force for citizens. On the one hand, human beings are not machines: They are aware of their digital twin and therefore are able to influence it throughout their lives. Because of their free will, human beings are in general difficult to predict. Dystopias of full control over individual behaviour are therefore unlikely to materialise. On the other hand, private firms are beginning to take advantage of the available digital twins of humans by monopolising data access and by commercialising predictive knowledge. This is problematic because, unlike machines, human beings cannot only benefit from but also suffer due to their digital twins as they attempt to shape their own lives. We illustrate these issues with some examples and arrive at two conclusions: It is in the public interest for people to be granted more property rights over their personal global digital twins, and publicly funded research needs to become more interdisciplinary, much like private firms that have already begun to perform interdisciplinary research.

Integrating and Synthesizing Technostress Research: A Meta-Analysis on Technostress Creators, Outcomes, and Usage Contexts - Nastjuk, I.; Trang, S.; Grummeck-Braamt, J.; Adam, M.; Tarafdar, M. (European Journal of Information Systems)

The technology-behavioral compensation effect: Unintended consequences of health technology adoption - Wolf, T.; Trang, S.; Weiger, W.; Trenz, M. (Journal of Information Technology)

Deflected by the Tin Foil Hat? Word-of-Mouth, Conspiracy Beliefs, and the Adoption of Public Health Apps - Krämer, T.; Weiger, W.; Trang, S.; Trenz, M. (Journal of Product Innovation Management)

Should I Really do That? Using Quantile Regression to Examine the Impact of Sanctions on Information Security Policy Compliance Behavior - Hengstler, S.; Kuehnel, S.; Masuch, K.; Nastjuk, I.; Trang, S. (Computers & Security)

Aggregating Human Domain Knowledge for Feature Ranking - Kornowicz, Jaroslaw; Thommes, Kirsten (Artificial Intelligence in HCI)

Oh my Goodness: Investigating the Goodness of Performance Appraisal Formats Between and Within Teams - Gutt, Jana Kim; Mehic, Miro; Thommes, Kirsten (Academy of Management Proceedings)

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia Amelie; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

Die Doppelwirkung von Information für klimafreundliches Handeln - Frick, Marc; Foese, Dario; Von Graevenitz, Kathrine; Kesternich, Martin; Wagner, Ulrich
Informationen sind für eine erfolgreiche Klimapolitik in doppelter Hinsicht wichtig: Sie werden benötigt, wenn Potenziale zur Vermeidung von Emissionen identifiziert und klimapolitische Instrumente ausgewählt werden. Und sie sind zentral, damit Bürger/innen selbst Entscheidungen im Sinne des Klimaschutzes treffen können.
Keywords: General Medicine

Nonfinancial Reporting and Real Sustainable Change: Relationship Status—It’s Complicated - Hahn, Rüdiger; Reimsbach, Daniel; Wickert, Christopher (Organization & Environment)
The relationship between nonfinancial reporting and real sustainable change within and beyond organizations is fraught with complication. Furthermore, all facets of the relationship have not been examined equally. The contributions of this special issue made substantive progress in this regard and draw our focus to several remaining complications—in particular, the societal impacts of nonfinancial reporting. With this introduction, we seek to move the conversation forward by proposing a framework that disentangles the linkages between nonfinancial reporting and real sustainable change at multiple levels of analysis. We highlight the distinction between sustainability-related outputs and outcomes that typically materialize at the firm level, and eventually lead to sustainable impact at the societal level. Future research should advance this distinction and scrutinize the impact of real sustainable change beyond firm-level outputs, study the organizational change processes from antecedents to impacts, and examine the interrelationships between different instruments to foster real sustainable change.
Keywords: Organizational Behavior and Human Resource Management; General Environmental Science